Are cytokines (IL-6, CRP and adiponectin) associated with bone mineral density in a young adult birth cohort? - Ana Maria Baptista Menezes; Paula Duarte Oliveira; Helen Gonçalves; Isabel O. Oliveira; Maria Cecilia F. Assunção; Luciana Tovo-Rodrigues; Gustavo Dias Ferreira; Fernando César Wehrmeister (BMC Musculoskeletal Disorders, 2018)
Abstract Background Studies have shown that cytokines play a role in bone remodeling. Methods In 1993, all hospital births occurred in Pelotas (Brazil) were identified and a total of 5249 newborns were included in the present cohort. Sub-samples of this cohort were visited during childhood and all members were traced at 11, 15, 18 and 22 years old. At 18 and 22 years the following biomarkers were measured: IL-6, CRP and adiponectin (the last one in a sub-sample) and bone mineral density (BMD-mg/cm2) was evaluated at 22 years. Crude regression analysis as well as adjusted for confounders (birth weight, pregnancy maternal smoking, gestational age, skin color, schooling, income, smoking, alcohol, physical activity, medical diagnosis of asthma, diabetes and hypertension, BMI, height, calcium intake, corticosteroid use, age at menarche, insulin and testosterone) were performed between the three biomarkers and the whole-body, lumbar spine and femoral BMD. Results No statistical significant association was found between IL-6 and CRP with BMD, in males. Significant inverse association in the adjusted analysis, among females, was found for the highest tertiles of CRP at 22 y (beta − 15.2 mg/cm2; 95% CI: -25.4; − 4.9; p = 004), of CRP and IL-6 at 22 years (beta − 20.0 mg/cm2; 95% CI: -31.7; − 8.3; p = 0.003), and of IL-6 and CRP at both ages (beta − 20.3 mg/cm2; 95% CI: -38.0; − 2.5; p = 0.001) with total body BMD. Significant association, among males, was also found between the highest tertile of adiponectin at 22 y (beta − 23.3 mg/cm2; 95% CI: -35.5; − 11.1; p = < 001; beta − 22.5 mg/cm2; 95% CI: -42.9; − 2.2; p = 0.03; and beta − 31.8 mg/cm2; 95% CI: -55.5; − 9.1; p = 0.006) and total body, lumbar spine and femur neck BMD, respectively; and, among females, − 17.8 mg/cm2; 95% CI: -34.9; − 0.9; p = 0.033, with lumbar spine BMD. Conclusion CRP at 22 years, in females, seems to be a marker for total body BMD; adiponectin at 22 years is also a marker for BMD at the three sites, in males, and for lumbar spine BMD, in females.